2021
DOI: 10.1111/imj.14872
|View full text |Cite
|
Sign up to set email alerts
|

Australian public hospital inpatient satisfaction related to early patient involvement and shared decision‐making in discharge planning

Abstract: Background Surveys of hospital inpatient satisfaction may help develop actionable plans for quality improvement, and patients have preferred to give feedback during admission at the point of service compared to after discharge. However, patient satisfaction measurement has often been done by questionnaires post‐discharge, and without focussing on an Australian general internal medicine setting. Aims To understand patients' perceptions of their admission experiences in an Australian public teaching hospital's g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…All of the papers in this collection were written in English and published. There are differences in several research locations that were found; two studies were conducted in Ethiopia [ 36 , 37 ], two studies in China [ 38 , 39 ], one study in Hong Kong [ 25 ], one study in the USA [ 40 ], one study from Germany, Switzerland, and Austria [ 41 ], one study in Indonesia [ 42 ], one study in Iran [ 26 ], one study in Korea [ 43 ] and one study in Australia [ 44 ]. Nine articles used a cross-sectional study method, one article was an experimental study, and one article was a cohort study.…”
Section: Content Analysis and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All of the papers in this collection were written in English and published. There are differences in several research locations that were found; two studies were conducted in Ethiopia [ 36 , 37 ], two studies in China [ 38 , 39 ], one study in Hong Kong [ 25 ], one study in the USA [ 40 ], one study from Germany, Switzerland, and Austria [ 41 ], one study in Indonesia [ 42 ], one study in Iran [ 26 ], one study in Korea [ 43 ] and one study in Australia [ 44 ]. Nine articles used a cross-sectional study method, one article was an experimental study, and one article was a cohort study.…”
Section: Content Analysis and Resultsmentioning
confidence: 99%
“…Six articles [ 25 , 26 , 39 , 41 , 42 , 43 ] out of the 11 articles met the review criteria, showing either that patient satisfaction with hospital services was more than 80%, or that an increase after intervention was higher than the national survey results. Conversely, five articles [ 36 , 37 , 38 , 40 , 44 ] demonstrated that the patients were less satisfied. Patient satisfaction was investigated with three types of study designs, namely cross-sectional studies (9 articles), experimental studies (1 article), and cohort studies (1 article).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations